The Intermarium in Ukrainian and Polish Foreign Policy Discourse - Polegkyi, Oleksii (East/West)

(untitled) (Canadian Institute of Ukrainian Studies University of Alberta, 2021)
The ongoing Russian-Ukrainian conflict, crises in the European Union (EU), and armed conflicts in the EU neighbourhood have influenced the prospects of future development in eastern and central Europe. A search for new security architecture on the margins of the EU and regional collaborations that prevail across formal EU borders have forced national elites in Poland and Ukraine to redefine their efforts regarding regional and security co-operation. Rationales for joining an Intermarium (a regional, transnational project involving successor states of the former Polish–Lithuanian Commonwealth countries) are based on the perception of a threat coming from Russia. This article analyzes the Intermarium concept, first, from the perspective of “geopolitical imaginary” with emphasis on periphery-centre relations and, second, in the light of regional “security dilemma” as it appears in attempt of “smaller” states to counteract Russian threats.